1990
DOI: 10.1002/eji.1830201203
|View full text |Cite
|
Sign up to set email alerts
|

In vitro analysis of age‐related changes in the developmental potential of bone marrow thymocyte progenitors

Abstract: Mechanisms underlying the age-related decrease in the developmental capacity of thymocyte progenitors from the bone marrow (BM) were analyzed, focussing on interaction of these cells with the thymic microenvironment. We employed the experimental model in which mixtures of young and old mouse BM cells, congenic for the Thy-1 marker, were seeded onto fetal thymus (FT) explains depleted of self lymphocytes and the levels of Thy-1+ cells developing from each of the two donor types were measured. When cells from yo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
20
0

Year Published

1997
1997
2007
2007

Publication Types

Select...
8
1
1

Relationship

1
9

Authors

Journals

citations
Cited by 57 publications
(21 citation statements)
references
References 12 publications
(8 reference statements)
1
20
0
Order By: Relevance
“…We could alternatively have made the more classical assumption, and explain decreased thymus production by decreasing the influx, , of progenitor cells (16,40,41). In that model the TREC content of TCR␣␤ ϩ and TCR␤ ϩ thymocytes, and the overall sj/ ␤-TREC ratio would be completely independent of age, because cells on average complete the same number of divisions in the thymus.…”
Section: Discussionmentioning
confidence: 99%
“…We could alternatively have made the more classical assumption, and explain decreased thymus production by decreasing the influx, , of progenitor cells (16,40,41). In that model the TREC content of TCR␣␤ ϩ and TCR␤ ϩ thymocytes, and the overall sj/ ␤-TREC ratio would be completely independent of age, because cells on average complete the same number of divisions in the thymus.…”
Section: Discussionmentioning
confidence: 99%
“…7 In support of the former, it has been suggested that decreased thymopoietic capacity is caused by the quantitative and/or qualitative alteration of progenitors with aging. [8][9][10][11] However, other investigators have reported that the number of immature CD44 ϩ CD25 Ϫ CD3 Ϫ CD4 Ϫ CD8 Ϫ ("triple-negative," TN) thymocytes is not significantly changed with aging. 12 Instead, increased apoptosis of immature thymocytes caused by insufficient amounts of the stroma-derived cytokine IL-7 reduces the number of thymocytes at subsequent stages of thymic differentiation, and IL-7 treatment normalizes thymopoiesis.…”
Section: Introductionmentioning
confidence: 98%
“…16,17 Studies using fetal thymic organ culture showed that aged BM is less efficient at reconstituting thymic lobes compared with young BM in competitive conditions. 18 It is possible that these data reflect reduced MPP frequency in aged BM, since MPPs can rapidly develop into thymocytes. However, because these studies did not assess purified populations, they did not distinguish between defects within individual hematopoietic progenitor cells versus age-related changes in frequencies of hematopoietic progenitor populations in the BM preparations.…”
Section: Introductionmentioning
confidence: 99%